Acculturation through sport: Different contexts different meanings. Issue 2 (4th March 2018) - Elbe, Anne-Marie; Hatzigeorgiadis, Antonis; Morela, Eleftheria; Ries, Francis; Kouli, Olga; Sanchez, Xavier
Abstract : Research on the role of sport as a social integrative agent for migrants has provided equivocal results. The purpose of this study was to investigate the relation between ethnic–cultural identity and sport environmental factors. Young migrant male athletes from two different societal and sport contexts were studied: migrants from Eastern European countries living in Greece ( n  = 60) and from Latin America living in Spain ( n  = 60). Participants completed measures of ethnic and cultural identity, task-oriented motivational climate, and autonomy-supportive coaching behaviour. Analysis of variance revealed that Eastern European inhabitants of Greece scored higher on fringe and assimilation, and lower on lack of interaction compared to Latin American inhabitants of Spain. In addition, for the former group, a mastery motivational climate and autonomy-supportive coaching predicted an integrative identity, whereas for the latter group, the motivational environment did not predict acculturation patterns. The results suggest that sport may serve different acculturation purposes, thus explaining to a degree the lack of consistent results regarding the integrative role of sport. The study provides preliminary support for the importance of the sport motivational environment for the facilitation of integration.